PENINGKATAN KUALITAS INFRASTRUKTUR PERMUKIMAN DAN PERSAMPAHAN MELALUI PENGUATAN KAPASITAS PEMERINTAH DESA DAN PEMBERDAYAAN MASYARAKAT DI DESA BOIDU KECAMATAN BULANGO UTARA KABUPATEN BONE BOLANGO - Koniyo, Yuniarti; Gobel, Muhammad Rizq; Sahaba, Muh. Alsere Bardian (Jurnal Abdi Insani, 2025)
The development of settlement infrastructure in rural areas, particularly in Boidu Village, still faces various challenges, including suboptimal waste management. Bone Bolango Regency generated 20,018.79 tons of waste in 2023, contributing to environmental issues. The lack of village government capacity and low community awareness remain major obstacles in managing waste and settlement infrastructure. This program aims to enhance the capacity of village governments and empower communities in managing settlement infrastructure and waste. The methods used include surveys, Focus Group Discussions (FGDs), socialization, and the establishment and mentoring of TPS3R management institutions. A participatory approach was implemented to increase community involvement in sustainable waste management efforts. The results indicate an improvement in community awareness regarding the importance of sustainable waste management. Socialization on Clean and Healthy Living Behavior (PHBS) successfully increased awareness among elementary school students. FGDs resulted in agreements on waste management strategies, while infrastructure planning assistance for TPS3R helped the village government formulate a Budget Plan (RAB). Furthermore, the community and village government’s commitment to independently managing TPS3R has strengthened. The implementation of this program demonstrates that strengthening village government capacity and community participation can improve settlement infrastructure and waste management. The program’s sustainability depends on government support and active community engagement.